Iron Deficiency and Stroke - J Gordon Millichap (Pediatric Neurology Briefs Publishers, 1997)
A series of six iron deficient children, 6 to 18 months of age, presenting with an ischemic stroke or venous thrombosis after a viral syndrome, are reported from the University of Saskatchewan, and the Children's Hospital of Eastern Ontario, Canada.